Transformasi Budaya Lokal Sebagai Strategi Marketing Product Majazi Indonesia - Septian Ardiyansyah Hidayat; O. Hasbiansyah (Bandung Conference Series: Communication Management, 2023)
Abstract. Based on data from Tinewss, the figures published on the Meta advertising tool show that Instagram has 99.15 million users in Indonesia in early 2022. Majazi Indonesia takes advantage of this potential to develop marketing for its business products. Sundanese local cultural transformation was chosen as Majazi Indonesia's marketing strategy. With this uniqueness, researchers are interested in examining Majazi Indonesia further. This study uses qualitative research methods with a case study approach and data collection techniques in the form of interviews, observation and documentation. Researchers take the results of research. (1) Instagram was chosen as a marketing medium as a form of adaptation to Majazi Indonesia's technological and information advances. (2) The process of marketing Majazi Indonesia products on Instagram is arranged in an orderly manner using academic theory. (3) Transformation of local Sundanese culture as a strategy is also carried out on the basis of the urgency of preserving Sundanese cultural values, motives of pride and forms of creativity. Abstrak. Berdasarkan Data dari Tinewss, bahwa angka yang dipublikasikan di alat periklanan Meta menunjukkan bahwa Instagram memiliki 99,15 juta pengguna di Indonesia pada awal 2022. Majazi Indonesia memanfaatkan potensi ini guna mengembangkan pemasaran produk bisnisnya. Transformasi budaya lokal Sunda dipilih sebagai strategi pemasaran Majazi Indonesia. Dengan keunikan tersebut, peneliti tertarik untuk meneliti Majazi Indonesia lebih jauh. Penelitian ini menggunakan metode penelitian kualitatif dengan pendekatan studi kasus adapaun teknik pengumpulan data berupa wawancara, observasi dan dokumentasi. Peneliti mengambil hasil penelitian. (1) Instagram dipilih sebagai media pemasaran sebagai bentuk adaptasi akan kemajuan teknologi dan informasi Majazi Indonesia. (2) Proses pemasaran produk Majazi Indonesia pada Instagram disusun secara tertata menggunakan teoritis akademis. (3) Transformasi budaya lokal Sunda sebagai strategi pun dilakukan atas dasar urgensi akan penjagaan nilai-nilai budaya Sunda, motif rasa bangga dan bentuk kreativitas.